Pemanfaatan Chatgpt Dalam Pembelajaran Ekonomi: Studi Kasus Tunggal di SMA - Surya Agus Haryanto Efendi; M. Nabiel Farica Eprion; Anel Musroy Gilbert Situmorang (Universitas Pendidikan Ganesha, 2026)
The rapid advancement of artificial intelligence has catalyzed the use of ChatGPT as an alternative learning resource in economics education. However, in-depth studies exploring the utilization of ChatGPT by senior high school students remain scarce. This study aims to describe the utilization of ChatGPT in economics learning based on students lived experiences. This research employed a single case study approach involving a Grade XII Social Science student at SMAN 1 Teluk Kuantan, selected via purposive sampling due to their profile as an information-rich, intensive user. Data were collected through semi-structured in-depth interviews and analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing). The findings indicate that ChatGPT is intensively utilized as a preliminary learning resource to support the comprehension of economics materials and task completion, primarily due to its time efficiency and accessibility. While ChatGPT accelerates initial comprehension, its usage requires critical awareness to mitigate the risk of dependency. Therefore, ChatGPT has the potential to serve as a supportive learning scaffolding in economics education when utilized critically and appropriately. The rapid advancement of artificial intelligence has catalyzed the use of ChatGPT as an alternative learning resource in economics education. However, in-depth studies exploring the utilization of ChatGPT by senior high school students remain scarce. This study aims to describe the utilization of ChatGPT in economics learning based on students lived experiences. This research employed a single case study approach involving a Grade XII Social Science student at SMAN 1 Teluk Kuantan, selected via purposive sampling due to their profile as an information-rich, intensive user. Data were collected through semi-structured in-depth interviews and analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing). The findings indicate that ChatGPT is intensively utilized as a preliminary learning resource to support the comprehension of economics materials and task completion, primarily due to its time efficiency and accessibility. While ChatGPT accelerates initial comprehension, its usage requires critical awareness to mitigate the risk of dependency. Therefore, ChatGPT has the potential to serve as a supportive learning scaffolding in economics education when utilized critically and appropriately.